2021
DOI: 10.1007/s10741-021-10115-8
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin receptor-neprilysin inhibition in patients with acute decompensated heart failure: an expert consensus position paper

Abstract: The short-term mortality and rehospitalization rates after admission for acute heart failure (AHF) remain high, despite the high level of adherence to contemporary practice guidelines. Observational data from non-randomized studies in AHF strongly support the in-hospital administration of oral evidence-based modifying chronic heart failure (HF) medications (i.e., b-blockers, ACE inhibitors, mineralocorticoid receptor antagonists) to reduce morbidity and mortality. Interestingly, a well-designed prospective ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The first 12 weeks after discharge is considered the at-risk phase. Almost 50% of rehospitalizations arise in this phase [ 3 ]. In ambulatory patients with HFrEF who remain symptomatic even after optimal medical treatment, the previous recommendation was ACEI or ARB which is currently replaced by sacubitril/valsartan [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The first 12 weeks after discharge is considered the at-risk phase. Almost 50% of rehospitalizations arise in this phase [ 3 ]. In ambulatory patients with HFrEF who remain symptomatic even after optimal medical treatment, the previous recommendation was ACEI or ARB which is currently replaced by sacubitril/valsartan [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…If initiated early in the hospitalization course instead of late or post-discharge initiation, it can save $811 per year. Inpatient initiation of the drug was associated with an improved overall cost-benefit ratio of $21,532 per quality-adjusted life-year (QALY) compared with continuous enalapril treatment for a lifetime [ 3 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Early initiation was well tolerated in both groups and maintenance of target dose 10-week post-randomization was comparable between the two groups. In light of these two clinical trials, an expert consensus position paper provided a comprehensive algorithm for in-hospital initiation of sac/val as well as for management of hypotension [ 57 ]. Ntalianis et al proposed four criteria for determination of clinical stability: (i) SBP equal to or greater than 100 mmHg for 6–12 h prior to the initiation, (ii) euvolemia, (iii) stable dose of intravenous diuretics for the past 6–12 h or preferably oral diuretics, (iv) no need for intravenous vasodilators, vasopressors, or inotropes for the last 6–12 h. In patients with SBP ≥ 100 mmHg, the lower dose of 24/26 mg should be preferred for initiation.…”
Section: Managementmentioning
confidence: 99%
“…In one of the latest expert consensuses, Ntalianis A et al described the role of sacubitril/valsartan in patients with ADHF [32]. The study concluded that sacubitril/valsartan is safe and well-tolerated and results in a significant reduction of NT-proBNP and reduction for HF rehospitalizations.…”
Section: Limitationsmentioning
confidence: 99%